2010
DOI: 10.1021/ie100888q
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Gelation Performance of Low Toxic PEI Cross-Linking PHPAM Gel Systems as Water Shutoff Agents in Low Temperature Reservoirs

Abstract: Using gel as the water shutoff agent has been widely reported in the aspect of enhanced oil recovery (EOR) of the development of mature oil fields. Cross-linkers such as chromium(III) acetate and phenol−formaldehyde are commonly used, but they are toxic. Today, use of low toxic polyethyleneimine (PEI) cross-linking a copolymer of acrylamide and tert-butyl acrylate (PAtBA) as the water shutoff gel is reported more but is mainly focused on its theoretical research and applications in high temperature reservoirs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 18 publications
(55 reference statements)
4
83
0
Order By: Relevance
“…The formed gel compresses water molecules contained in the gel network structure and shrinks its volume to exclude water molecules out. 19 Moradi-Araghi et al 10 reported that the gel syneresis could be also caused by the alteration of gel mechanical property due to the reaction between carboxyl groups in polymer molecules and bivalent or trivalent ions. However, due to the application of the deionized water in the screening test, the effect of metallic ions on the gel formation was weak; hence the excessive cross-linking was blamed for the gel syneresis.…”
Section: Resultsmentioning
confidence: 99%
“…The formed gel compresses water molecules contained in the gel network structure and shrinks its volume to exclude water molecules out. 19 Moradi-Araghi et al 10 reported that the gel syneresis could be also caused by the alteration of gel mechanical property due to the reaction between carboxyl groups in polymer molecules and bivalent or trivalent ions. However, due to the application of the deionized water in the screening test, the effect of metallic ions on the gel formation was weak; hence the excessive cross-linking was blamed for the gel syneresis.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction between HPAM and PEI can be explained as imine nitrogen from PEI attacking the carbonyl carbon attached to the amide group of the polymer (Fig. 3) (Jia et al 2010). That creates chemical bonds which are much stronger than ionic bonds.…”
Section: Bulk Experimentsmentioning
confidence: 99%
“…e effect of temperature ( in degree kelvin) can also be incorporated in (8) and Arrhenius model [19] can be utilized to connect with which is as follows: where is an apparent activation energy and is the gas constant. erefore, the combination of (10) and (11), then we get…”
Section: Development Of Mathematical Modelmentioning
confidence: 99%
“…is crosslinking is believed to rely on coordination covalent bonding. It should be mentioned that Cr (III) based polymer gel system were reported to be stable at temperatures up to 300 ∘ F [8][9][10]. e organically crosslinked gels developed using phenol and formaldehyde crosslinkers are thermally stable under harsh environmental conditions.…”
Section: Introductionmentioning
confidence: 99%